Sleep Timing and Risk of Dementia Among the Chinese Elderly in an Urban Community: The Shanghai Aging Study - Li, Xiantao; Ding, Ding; Zhao, Qianhua; Wu, Wanqing; Xiao, Zhenxu; Luo, Jianfeng; Yaffe, Kristine; Leng, Yue (Frontiers in Neurology, 2021)
Background: Growing evidence suggested a link between poor sleep quality and increased risk of dementia. However, little is known about the association between sleep timing, an important behavior marker of circadian rhythms, and dementia risk in older adults, and whether this is independent of sleep duration or quality. Methods: We included data from 1051 community-dwelling older men and women (aged≥ 60y) without dementia from the Shanghai Aging Study. At baseline, participants reported sleep timing, duration and quality using the Chinese version of the Pittsburgh Sleep Quality Index (CPSQI). Dementia diagnosis over the following 7.3 years was determined by neurologists using DSM-IV criteria. We used Cox proportional hazards models to examine the association between bedtime (before 9pm, after 11pm vs. 9-11pm), rise time (before 6am, after 8am vs. 6-8am), and risk of dementia. Results: 238 (22.8%), 675 (64.5%) and 133 (12.7%) participants reported going to bed before 9pm, between 9-11pm, and after 11pm, respectively while 272 (26%), 626 (59.9%) and 148 (14.2%) reported getting up before 6am, between 6-8am, and after 8am, respectively. Participants who reported going to bed earlier had lower education level, were less likely to be smokers, more likely to have hypertension or diabetes, and had longer sleep duration but poorer sleep quality compared to those who reported later bedtime. We found 47 incident dementia among 584 participants followed up over averagely 7.3 years. After adjustment for demographics, education, income, body mass index, depressive symptoms, smoking, alcohol use, physical activity, comorbidities, APOE4 genotype, and baseline MMSE, those with a bedtime of before 9pm were two times as likely to develop dementia [hazard ratio (HR)=2.16 (95%CI: 1.06-4.40)], compared to those going to bed between 9-11pm. Later bedtime (i.e. after 11pm) showed the opposite but non-significant association with dementia risk (HR=0.15, 95%CI: 0.02-1.29). We did not find an association for rise time and risk of dementia. Conclusion: Earlier sleep timing in non-demented older adults was associated with an increased risk of dementia. Future studies should examine the underlying mechanisms of this association and explore the usefulness of sleep timing as a preclinical marker for dementia.